Analisa Kinerja Lalu Lintas Simpang Tak Bersinyal pada Ruas Jalan Tirto Rahayu, Tlogomas Landungsari - Seran Maia , Gerjulani Elisabeth; Arifianto, Andy Kristafi ; Rahma, Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Intersections are part of roads where currents from various directions or directions meet. That is why at the intersection there is a conflict between the currents from opposite directions and cutting each other, resulting in congestion along the arm intersection.At the intersection, congestion is often caused by side obstacles, the high population of vehicles that is not balanced with the availability of road facilities. one of the intersections that at certain times experiences conflicts and buildup of vehicles, that is at the Tirto Rahayu intersection in Malang, at this intersection often there is a buildup of vehicles during rush hour. The purpose of this study is to determine the characteristics of the intersection, the level of service and alternative handling. The method used is quantitative descriptive. The results of this study indicate that the traffic volume characteristics in the first week are greater than the second week with the number of the first week: 974.6 pcu / hour and the second week: 843.1 pcu / hour, with a capacity of 1461.6. The degree of saturation is 0.62 and the level of service is C.